2013
DOI: 10.1016/j.neuropharm.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Perseverative behavior in rats with methamphetamine-induced neurotoxicity

Abstract: Methamphetamine induces monoamine depletions thought to contribute to cognitive and behavioral dysfunctions. Previously, we reported that methamphetamine-induced neurotoxicity is associated with impaired formation of stimulus-response associations. Additionally, subjective observations suggested that behavioral flexibility might be affected. Thus, the present study examined whether methamphetamine neurotoxicity induces perseverative behavior. Rats were pretreated with (±)-methamphetamine (4×10 mg/kg, 2-hr inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…Blockade of D 1 R or D 2 R in mPFC in rat reduced behavioural flexibility; it acted primarily by increasing perseveration (Floresco et al, 2006), which is not tested in the LNR paradigm. It is therefore possible that in reversal learning tasks, mPFC mainly contributes to overcoming perseveration rather than to LNR (Allen and Leri, 2014;Son et al, 2013). Furthermore, neurotransmitters other than DA, in particular serotonin, may modulate mPFC-dependent cognitive flexibility (Clarke et al, 2004;van der Plasse and Feenstra, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of D 1 R or D 2 R in mPFC in rat reduced behavioural flexibility; it acted primarily by increasing perseveration (Floresco et al, 2006), which is not tested in the LNR paradigm. It is therefore possible that in reversal learning tasks, mPFC mainly contributes to overcoming perseveration rather than to LNR (Allen and Leri, 2014;Son et al, 2013). Furthermore, neurotransmitters other than DA, in particular serotonin, may modulate mPFC-dependent cognitive flexibility (Clarke et al, 2004;van der Plasse and Feenstra, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Later on, the term may have come to signify reverberating neuronal activity that occurred as part of a 'dual process' in memory consolidation (McGaugh, 2000). However, the term now is typically used in descriptions of more pathological behaviours occurring as a result of damage to specific circuits in the CNS Sotres-Bayon et al, 2004;Son et al, 2013 (Thomas et al, 2016), and it has also been shown that growing up in an enriched laboratory environment (i.e. a more natural environment) lessens perseveration (Campbell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were treated with a neurotoxic regimen of ( ± )-METHHCl (4 Â 10 mg/kg, free base, at 2-h intervals, s.c.; NIDA, Research Triangle Park, NC, USA) over the course of 1 day as previously described (Daberkow et al, 2008;Son et al, 2013). The day after treatment, rats were returned to their home cages and given free access to food and water until training began.…”
Section: Meth Pretreatmentmentioning
confidence: 99%
“…DAT and SERT autoradiography was performed as detailed previously (Barker-Haliski et al, 2012a;Boja et al, 1992;Pastuzyn et al, 2012;Son et al, 2013). For striatal sections, the buffer contained fluoxetine (Sigma-Aldrich, St Louis, MO, USA) to block binding to the SERT, whereas for prefrontal cortical (PFC) sections, fluoxetine was omitted from the buffer, as PFC sections incubated in buffer containing fluoxetine showed no staining (data not shown).…”
Section: Da and Sert Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation